PEMANFAATAN JBCLASS UNTUK MENINGKATKAN MOTIVASI BELAJAR BAHASA INGGRIS PESERTA DIDIK SELAMA MASA PANDEMI COVID-19 - Yuni Lestari (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2020)
This article aims to enhance the motivation in learning English of the tenth grade Students of SMA N 7 Yogyakarta by using JBClass during COVID-19 pandemic. This article is a best practice which was conducted in the 2nd semester, 2019-2020 academic year. The subjects were the tenth grade students of SMA N 7 Yogyakarta which consists of 8 classes (6 science classes and 2 social classes). They were 280 students (178 girls and 102 boys). The steps of problem solving in this best practice by using JBClass as e-learning during COVID-19 pandemic. The instruments of this best practice were taken from the features in JBClass namely material, assignment, evaluation and score recapitulation. The result shows that using JBClass in e-learning during COVID-19 pandemic can enhance the motivation in learning English of the tenth grade students of SMA N 7 Yogyakarta, 2019-2020 academic year. This enhancement can be seen from the higher of mean from each class’ English score and the timeliness in submitting of the assignment and evaluation in e-learning using JBClass during COVID-19 pandemic.